The Experimental Characteristics and Evaluation of Nylon-12 in Erosion Process - Debnath, U. K.; Chowdhury, M. A.; Nuruzzaman, D. M. (ASTM International, 2017)
Polymer materials are used in a wide range of applications. The erosion properties of nylon-12 were analyzed in this study. Randomly-shaped sand (SiO2) particles of various sizes (300–355 lm, 355–500 lm, and 500–600 lm) were selected as erosive elements. Impingement angles between 15 and 90_, impingement velocities between 30 and 50 m/s, and stand-off distances 15–25mm at ambient temperature were tested. During testing, the maximum erosion of the tested polymer composite occurred at 30_ angle of impingement, indicating a ductile nature of the test material. Erosion increased with impact velocity and decreased with stand-off distance. The erosion rate varies from approximately 5 to 1600 mg/kg at different combinations of impact velocity, impact angle, and other related parameters. The mean S/N ratio was found to be _41.35 dB, which reflects the average erosion rate under different test conditions. Test results were evaluated using Taguchi’s concept to minimize the observations needed, and analysis of variance (ANOVA) was used to identify interactions between tested parameters and identify the most significant parameters. Surface damage was examined using scanning electronic microscopy (SEM) to examine the nature of the wear behavior. The morphology of tested material showed micro cutting, micro cracking, ploughing, and deformation as dominating damage characteristics of impacting surfaces.